Tekemällä matkailun kulttuuriseen kestävyyteen: Ongelmia ja niiden hallintaa Utsjoen kirkonkylässä - Mällinen, Maria-Riitta; Sarkki, Simo (Suomen matkailututkimuksen seura ry, 2014)
Sustainable tourism studies often focus on economic, ecological and social dimensions of sustainability while there is a lack of theoretical understanding on how cultural sustainability is constituted. Here we see that cultural meanings related to tourism among indigenous and other local people are born via everyday doing in the environment, and on the other hand, in performing the local way of life for tourists. The study examines how local people (sámi and non-sámi) of Utsjoki (Ochejohka) experience problems concerning culturally sustainable tourism including unwanted changes in possibilities for everyday doing in the nature; discrepancy between culture performed for tourists and for oneself and other locals. Empirically identified solutions for enhancing sustainable tourism include sustainable products, respect for the local, active governance, and collaboration. We view these empirically defined problems and solutions in contexts of the ‘doing culture in everyday practices’, and argue that this is an avenue for new understanding of how culturally sustainable can be defined and what implications it has especially for the research on culturally sustainable tourism regarding rural and indigenous people. Doing culturally sustainable tourism: problems and solutions for their governance in Utsjoki, Finland Sustainable tourism studies often focus on economic, ecological and social dimensions of sustainability while there is a lack of theoretical understanding on how cultural sustainability is constituted. Here we see that cultural meanings related to tourism among indigenous and other local people are born via everyday doing in the environment, and on the other hand, in performing the local way of life for tourists. The study examines how local people (sámi and non-sámi) of Utsjoki (Ochejohka) experience problems concerning culturally sustainable tourism including unwanted changes in possibilities for everyday doing in the nature; discrepancy between culture performed for tourists and for oneself and other locals. Empirically identified solutions for enhancing sustainable tourism include sustainable products, respect for the local, active governance, and collaboration. We view these empirically defined problems and solutions in contexts of the ‘doing culture in everyday practices’, and argue that this is an avenue for new understanding of how culturally sustainable can be defined and what implications it has especially for the research on culturally sustainable tourism regarding rural and indigenous people.